(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Libraries have boosted their services with the introduction of ICT. This arena of advanced technology helps the users irrespective of geographical boundaries on real time basis. Mobile landscape has broadened considerably and currently libraries are exploring to launch mobile technology. Mobile technology has connected library to its world readers within short awhile. This digital system has brought about revolutionized change. The current paper discusses leading methods that Advanced libraries are incorporating to deliver services through mobile devices. Rising mobile apps are paving way to be user friendly and accessible to massive context of resources of the library. In the current paper we’ve focussed on mobile application and challenges in library services.